Advancing musculoskeletal research with nanoscience - Brown, C (2013)
Nanoscience has arrived. Biological applications of nanoscience are particularly prominent and can be useful in a range of disciplines. Advances in nanoscience are underpinning breakthroughs in biomedical research and are beginning to be adopted by the rheumatology and musculoskeletal science communities. Within these fields, nanoscience can be applied to imaging, drug delivery, implant development, regenerative medicine, and the characterization of nanoscale features of cells, matrices and biomaterials. Nanoscience and nanotechnology also provide means by which the interaction of cells with their environment can be studied, thereby increasing the understanding of disease and regenerative processes. Although its potential is clear, nanoscience research tends to be highly technical, generally targeting an audience of physicists, chemists, materials scientists and engineers, and is difficult for a general audience to follow. This Review aims to step back from the most technical aspects of nanoscience and provide a widely accessible view of how it can be applied to advance the field of rheumatology, with an emphasis on technologies that can have an immediate impact on rheumatology and musculoskeletal research. © 2013 Macmillan Publishers Limited.